Weak Complexes of S and Se: Interaction and Complex Formation of Iodide Ions with Some Arenesulfonyl Chlorides. - SALAMA , S.B; WASIF, S. (Asian Journal of Chemistry, 2010)
Mixtures of arylsulfonyl compounds with iodide ions were investigated in acetonitrile. They gave rise to 1 : 1 yellow coloured complex species which absorbed at 286 and 360 nm. The appearance of the yellow species is time dependent and is first order in [I–] and in [sulfur compound] and has an E≠a ranging from 10–20 kcal. When mixtures were left for longer periods an equilibrium was reached and the formation constants for benzenesulfonyl chloride, p-methoxy, p-toluene, 4-bromo and 4-chloro were determined with iodide ions over range of temperatures (5º–35ºC). The thermodynamic parameters of the complex species agree with those of charge transfer complexes. Chloride and bromide ions react with the yellow species to give the original reactants.